Impact of Obesity on Short-Term Outcomes Following Catheter Ablation for Atrial Fibrillation in Patients with Heart Failure: A Population-Based Study of Nationwide Inpatient Sample 2005-2018 - Yu, Fuling; Ning, Ruobing; Zhang, Meijin; Zeng, Yongjun (International Heart Journal, 2025)
This study aimed to evaluate the impact of obesity on in-hospital outcomes of patients with HF undergoing AF catheter ablation. This population-based, retrospective observational study extracted data from the US Nationwide Inpatient Sample (NIS) database 2005-2018. Patients ≥ 20 years with HF and undergoing catheter ablation for AF were eligible for inclusion. Propensity-score matching (PSM) was utilized to balance the baseline characteristics between obese and non-obese groups. Univariate and multivariable regression analyses were used to determine the associations between obese status and other variables with the in-hospital outcomes. These outcomes included non-home discharge, prolonged length of stay (LOS), complications, and a composite outcome that encompassed these outcomes along with in-hospital mortality. A total of 18,751 patients were included. After PSM, 8,014 patients remained in the study sample. The mean age was 64.6 ± 0.1 years. After adjustment, significant association was detected between obesity and greater odds of non-home discharge (adjusted odd ratio [aOR] = 1.18), prolonged LOS (aOR = 1.18), complications (aOR = 1.30), respiratory failure/mechanical ventilation (aOR = 1.56) and acute kidney injury (AKI) (aOR = 1.28), central nervous system and peripheral neuropathy (aOR = 1.33), and transient ischemic attack (aOR = 8.16), as well as poor composite outcome (aOR = 1.28) compared with non-obese patients. In US patients with HF undergoing AF catheter ablation, obesity is associated with a higher risk for non-home discharge, prolonged LOS, and several major complications. Clinicians should exercise heightened vigilance when administering therapy to this subgroup of patients.